The periphery: unstable fragments of the city lived - Lindon, Alicia (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This paper presents a theoretical-methodological approach to the periphery from the daily spatial experiences of its inhabitants. It implies a multiple inversion of the common point of view of urban studies. On the one hand, space and time are conceived as lived. On the other, the method is inverted by taking the inhabitants’ life narratives to approach the geographical reality, i.e., the discourses on places rather than the records of places. The first part addresses the periphery as dense fragments that express unstable states of urban areas, always marked by the tension between peripheral change and order. Then, the proposal explores the approach to the periphery lived from the analysis of the inhabitants’ spatial experiences through the peripheral anchoring of their individual and family biographical events and the establishment of peripheral chronotopes in local narratives.